Integrating mental health into climate change adaptation policies - Eissa,M; Newberry,Le Vay J; Jennings,N; Lawrance,E; Massazza,A (Grantham Institute, Imperial College London, 2025)
This report was commissioned by United for Global Mental Health in collaboration with the Climate Cares Centre at Imperial College London to better understand the extent to which mental health has been integrated into national adaptation policies.